Education on the Use of Iot Technology for Energy Audit and Management Within the Context of Conservation and Efficiency - Wahyu Sejati; Vivi Melinda (International Transactions on Education Technology (ITEE), 2023)
Education on the use of IoT technology for energy audit and management within the context of conservation and efficiency The demand for electrical energy rises in direct proportion to a region's economy. The basic electricity rate rises in response to the steadily growing demand for electrical energy. Increased use of electrical energy is a result of wasteful conduct and a disregard for equipment standardization. increases the utilization of electrical energy. The local population still does not appear to be concerned or aware of how crucial it is to keep the electrical supply sustainable.Many studies that are pertinent to energy efficiency and conservation education have been conducted.Thus, the community needs to be informed of this information in order to, among other things, increase understanding, encourage the community to behave economically, conduct audits, and manage electrical energy in accordance with standardized practices. SMK N 1 Brebes, a vocational school for electrical and electronics, is a setting that is pertinent to the use of this technology. The development in students' abilities after engaging in this activity shows that it has delivered education in the form of reading material and energy management practice.